Ethical leadership and job satisfaction: extending the dual mediation mechanism - Udin, Udin; Nurfitri, Dini; Shaikh, Mohsin (BISMA (Bisnis dan Manajemen), 2023)
Ethical leadership is crucial for the success and sustainability of modern organisation s. Therefore, this study aims to explore and investigate the effect of ethical leadership on job satisfaction. Additionally, this study investigates the mediating roles of work stress and work-life balance (WLB) in the relationship between ethical leadership and job satisfaction. Using a cross-sectional design and self-administered questionnaire, the data are collected from 110 employees working in the private hospital in Indonesia and analysed utilising Structural Equation Modeling (SEM) with SmartPLS 3.2 software. The results show that ethical leadership is positively related to WLB as well as job satisfaction, and negatively to work stress. In addition, WLB positively affects job satisfaction, whereas work stress has no significant effect. Given indirect relationships and, more specifically, the findings indicate that WLB fully mediates the effect of ethical leadership on job satisfaction. The findings of this study provide practical implications that ethical leadership supports and empowers employees to experiment and try new things for happiness at work and in their personal lives. This implies that the leader’s concern reinforces a sense of belonging and increases job satisfaction.